2003
DOI: 10.1002/joc.900
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the South American summer monsoon associated with the 1997–99 El Niño–southern oscillation

Abstract: We describe the rainfall and circulation anomalies of the South American summer monsoon (SASM) during December-January-February (DJF) of 1997-98 (El Niño) and 1998-99 (La Niña). The most pronounced rainfall signals in DJF 1997-98 include (a) excessive rainfall over northern Peru and Ecuador, (b) deficient rainfall over northern and central Brazil, and (c) above-normal rainfall over southeastern subtropical South America. The rainfall anomalies in (a) and (b) are associated with the excitation of an anomalous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Few studies using the PACS-SONET, reanalyses, and regional modeling have suggested enhanced SALLJ activity during 1998 as compared to 1999 (Douglas et al 1999;Misra et al 2000;Saulo et al 2000;Vernekar et al 2003;Marengo et al 2002;Lau and Zhou 2003) exhibits substantial interannual variability. Both reanalyses and observations suggest fewer episodes of SALLJs in 1999 as compared to 1998, but the lack of observations during other El Niño events does not allow for a general conclusion between the presence of El Niño and a more active SALLJ season.…”
Section: ) Annual and Diurnal Cyclementioning
confidence: 99%
“…Few studies using the PACS-SONET, reanalyses, and regional modeling have suggested enhanced SALLJ activity during 1998 as compared to 1999 (Douglas et al 1999;Misra et al 2000;Saulo et al 2000;Vernekar et al 2003;Marengo et al 2002;Lau and Zhou 2003) exhibits substantial interannual variability. Both reanalyses and observations suggest fewer episodes of SALLJs in 1999 as compared to 1998, but the lack of observations during other El Niño events does not allow for a general conclusion between the presence of El Niño and a more active SALLJ season.…”
Section: ) Annual and Diurnal Cyclementioning
confidence: 99%
“…For instance, Berbery and Barros (2002) suggested that during the austral summer of the three more relevant El Niños (EN) that occurred in the 1980-2000 period, the large-scale patterns showed increased southward component of moisture flux over La Plata Basin. Lau and Zhou (2003) observed a reduction of rainfall over the Amazon associated with a poleward shift of the South American monsoon circulation and rainfall system during the 1997/98 El Niño. They indicated that the Bolivian high was hydrostatically enhanced by the anomalous tropospheric warm ridge extending from the Niño-3 region to the Altiplano Plateau.…”
Section: Introductionmentioning
confidence: 96%
“…They found a much stronger SALLJ penetrated deeply into the extratropics along the eastern side of the subtropical Andes, coinciding with the reinforcement of the upper tropospheric subtropical westerly and the local meridional overturning. Marengo et al (2004), Lau andZhou (2003) andNieto Ferreira et al (2003) have also indicated that the 1997/98 EN had more frequent and strong SALLJ episodes when compared to the 1999/2000 La Niña (LN) event. Silva and Ambrizzi (2006) verified that during the event of 1997/98 a low-level anomalous anticyclonic circulation over the central part of Brazil enhanced the wind in the core of the SALLJ and displaced the jet to the Northern Argentina and South of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In ENSO warm phases (El Nino), it is moved eastwards as far as to NEB, resulting in a descending dry air mass. At the same time, the subtropical anticyclones on both sides of the ITCZ are strengthened [26].…”
Section: Study Area: Northeastern Brazil (Neb)mentioning
confidence: 99%
“…Extreme climate conditions, such as prolonged droughts due to climatic anomalies, are associated with an eastward shift of the Walker circulation and, at the same time, with a warming of the middle and upper troposphere, due to increasing SST in the Eastern Pacific [26]. Both processes lead to a temperature increase in the troposphere east of the Andes.…”
Section: Study Area: Northeastern Brazil (Neb)mentioning
confidence: 99%